Cost of breast cancer diagnosis and treatment in India: a scoping review protocol. Issue 3 (16th March 2022) - Barathe, Priyanka Chandrakant; Haridas, Herosh T; Soni, Priya; Kudiya, Krithi Kariya; Krishnan, Jisha B; Dhyani, Vijay Shree; Rajendran, Ambigai; Sirur, Andria J N; Pundir, Prachi
Abstract : Introduction: Breast cancer is the foremost cause for mortality among women. The non-communicable disease imposes significant economic expenses to communities. Its economic impact includes both direct and indirect healthcare costs. This scoping review will map key concepts underpinning the current direct and indirect expenses of breast cancer in India. Methods and analysis: This scoping review will follow 'Arksey and O'Malley's' approach and updated methodological guidance from the Joanna Briggs Institute. The Cochrane library, Econ Papers, Embase, ProQuest central, PubMed and SCOPUS will be searched for peer-reviewed scientific journal publications from the year 2000 to 2021. Reference lists of included articles and preprint repositories will be searched for additional and unpublished literature. Independent screening (title, abstract and full text) and data extraction will be carried out against the defined inclusion criteria. The results will be narratively summarised and charted under the conceptual areas of this scoping review. The research gaps and scope for future research on the topic will be identified. Findings will be reported using the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews. Ethics and dissemination: Ethics clearance will not be obligatory because this scoping review will only involve publicly available data. The review's findings will be disseminated through social media and a presentation in a national or international conference related to economics and healthcare. The findings will be published in a scientific journal that is peer-reviewed.